Pengaruh Lingkungan Kerja dan Kedisiplinan Kerja Terhadap Kepuasan Kerja Karyawan Pada PT. Pertamina Lubricants - Neny, Neny; Lubis, Andriani (Jurnal Ilmiah Wahana Pendidikan, 2024)
The0objective of this0study is to determine0if there is a0correlation between the work0environment0(X1) and work discipline0 (X2) and job satisfaction (Y) among workers of PT. 0Pertamina0Lubricants, Jakarta. The study0used a quantitative methodology, with0questionnaires as the primary means of data collecting. The study used a sample size of 56 respondents. Data analysis techniques in this research are validity0test, reliability0test, correlation coefficient0analysis, multiple0linear regression0analysis, t0test,F0test, and0determination analysis0using the SPSS0250program. The0research results show that the t0value for0the work environment variable0 (X1) is03.168 > ttable (2.005). Consequently, H1 is deemed valid but H01 is deemed invalid, indicating that0the work0environment has0a substantial and0beneficial impact on the job0satisfaction0of PT employees. Pertamina Lubricants. The calculated value0for the work0discipline variable0(X2) is01.400 < ttable (2.005). This means that H2 is rejected0and H02 is0accepted, which means0that work0discipline has0no0significant influence0on job satisfaction of PT employees. Pertamina Lubricants. Meanwhile, the Fcount value is 57.051>Ftable 3.172. Consequently, the0null hypothesis0H03 is refuted while the alternative0hypothesis H3 is supported. The0analysis indicates a notable combined impact of the work environment0and work0discipline on0employee job0satisfaction at0PT. Pertamina Lubricants. The coefficient of determination (R2) is 68.3%, indicating that 68.3% of the variation in the dependent variable can be explained by the work0environment and0work0discipline. The0remaining 31.7% of the variation is attributed to0other factors0that were0not0included in0this0study.